Pengaruh Dimensi Fraud Crowe Pentagon terhadap Kecurangan Akademik Mahasiswa - Apriyeni , Yolanda; Aprila, Nila (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to determine how aspects of the Fraud Crowe Pentagon affect academic fraud among students. The sample in this study were undergraduate accounting students of the Faculty of Economics and Business, Bengkulu University. The sampling technique used was purposive sampling, with criteria including undergraduate accounting students who are still active, registered at Bengkulu University, accounting students who have taken behavioral accounting and auditing I and II courses, and accounting students in semesters 5, 7, and 9. The sample used was 100 participants obtained by distributing questionnaires via Google Form. SmartPLS 4 is the analysis tool used in this study. The results of this study indicate that fraud is not influenced by pressure, rationalization, competence, or arrogance, but is influenced by opportunity. Opportunity has a positive and significant effect of 0.001 on academic fraud of undergraduate accounting students at Bengkulu University.